Uma sequência didática em abordagem decolonial: a farinha de mandioca, os conhecimentos indígenas e o ensino de química - Silva, Pedro Henrique Diggelmann da (Universidade Federal de São Carlos, 2024)
The current configuration of schools in our society grants the applied curriculum the power to transmit content and knowledge, but also positions and conceptions of the world. These conceptions can reinforce an overly technicist and Eurocentric view of knowledge. This paper offers a reflection on these conceptions that are transmitted by the teaching of chemistry in school. To this end, based on the concept of decolonial teaching as a theoretical foundation, a Didactic Sequence was constructed, guided by the Three Pedagogical Moments methodology, as well as an Activity Booklet, centered on the chemical content of separation of mixtures and its tools, using the processes of making manioc flour and its relationship with the indigenous communities of Brazil as a theme. The Didactic Sequence includes problematizations in the form of videos and texts that discuss indigenous knowledge related to the content and theme, while the Activity Booklet is made up of application activities, such as a questionnaire, essay proposal and experiment, aimed at promoting an understanding of the content from the perspective of decoloniality. The construction of this Didactic Sequence is supported by a brief bibliographical review on decoloniality and decolonial teaching and a delimitation of the relationships between the process of making manioc flour and the physical-chemical procedures for separating mixtures, highlighting the historical and cultural importance of manioc in Brazilian food and the indigenous role in handling this food. The Didactic Sequence constructed is understood as an adaptable model that presents the viability of the decolonial approach with the manioc flour theme, offering a starting point for teachers and researchers that intend to delve deeper into the potential of the approach, theme or methodology, either theoretically, with bibliographic reviews, or practically, through the application of this sequence, which, though not being covered in this work, is a relevant perspective for future works.
Didactic sequence with a decolonial approach: manioc flour, indigenous knowledge and chemistry teaching
Keywords: Três Momentos Pedagógicos; Ensino Decolonial; Separação de Misturas; Decolonial Education; Three Pedagogical Moments; Separation of Mixtures; CIENCIAS EXATAS E DA TERRA::QUIMICA